KEANEKARAGAMAN TUMBUHAN Durio spp. MENURUT PERSPEKTIF LOKAL MASYARAKAT DAYAK - Priyanti, Priyanti (MAJALAH ILMIAH WIDYA, 2012)
Durio is one of the members of Bombacaceae. It is famous as durian. The Durio diversity center located on Borneo island,inhabited by native tribes, such as: Banjar, Kutai and Dayak. Dayak tribe settled the area in planting various kinds of fruit trees, suchas: Durio. The purpose of this study was to assess local knowledge of Dayak community about the diversity of Durio that grew aroundtheir homes. The method used literature study. The results show that: (1) the Dayak people have taken advantage of about 9 Duriospecies for food and pharmaceutical raw materials. (2) The names of the durian are awarded based on observations in nature. (3)Various efforts in preserving the farm management of Durio is simpukng or lembo (Benuaq and Tunjung) and stangu (Dayak Gaai).(4) The farm management can be developed among the indigenous peoples and local governments so that durian fruit supply athome and abroad.